The analysis of quantitative traits of self-pollinated lines of waxy maize (Zea Mays L. Ceratina) - G. Ya. Krivosheev; A. S. Ignatiev (Зерновое хозяйство России, 2019)
The grain productivity and elements of yield structure of 34 new self-pollinated lines of the subspecies of waxy maize (Zea mays L. ceratina) have been studied. The elements of structure varied according to their effect on yield formation of these self-pollinated lines. The traits “number of cobs per plant”, “number of kernels per cob”, “number of rows with kernels” were of the great value, the trait “1000-kernels weight” was of the small value. The correlation analysis and the analysis of surface graphs identified the possibility to combine the largest values of complementary traits of the waxy maize lines. In 2015–2017 there was no any correlation between the traits “number of cobs per plant” and “weight of one cob” (r = –0.17±0.17…+0.16±0.17). Grain productivity of the lines increased proportionally to the increase of cob weight and a number of cobs per plant. In 2015 there was an average negative correlation between the traits “1000-kernels weight” and “number of kernels per cob” (r = –0.37±0.16), and in 2016–2017 there was no any correlation at all (r = –0.12±0.18, r = –0.10±0.18). The maximum productivity was formed at the combination of maximum values of the traits (241 g of “1000-kernels weight”; 540 pc. of “number of kernels per cob”). There was a tendency to the increase of a number of kernels together with the rise of kernel rows (r = 0.18±0.17…0.32±0.17). The largest productivity was formed at a maximum quantity of kernel rows (18 pc) and optimal quantity of kernels per row (30 pc). There was no correlation between “weight of one cob” and “number of kernel per cob” (r = –0.18±0.17…+0.27±0.17). The combination of the maximum values of the productivity traits promoted the formation of maximum grain yield. There have been identified the new self-pollinated lines of waxy maize “24/78”, “Wx2MP”, “21/82 (1)”, “25/75” with high grain productivity (1.0–2.42 t/ha) and large values of the productivity traits.